2014
DOI: 10.1007/s00345-014-1395-1
|View full text |Cite
|
Sign up to set email alerts
|

Update on lasers in urology 2014: current assessment on holmium:yttrium–aluminum–garnet (Ho:YAG) laser lithotripter settings and laser fibers

Abstract: Many technical factors influence the performance of holmium laser lithotripsy. Knowing and understanding these controllable parameters allows the urologist to perform a laser lithotripsy procedure safely, efficiently, and with few complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(88 citation statements)
references
References 44 publications
1
82
0
5
Order By: Relevance
“…Furthermore, newer techniques such as intracorpor eal laser lithotripsy using highwattage holmium lasers to 'dust' stones are emerging, which might obviate the need for fragment retrieval in some patients. 64,65 Finally, the routine deployment of a UAS is not without its risks. 66 Until level 1 evidence for the safety and effectiveness of this procedure emerges, the indications for use of a UAS and retrieval will likely remain very much influenced by both patientrelated and stonerelated factors.…”
Section: Active Retrieval Of Fragmentsmentioning
confidence: 99%
“…Furthermore, newer techniques such as intracorpor eal laser lithotripsy using highwattage holmium lasers to 'dust' stones are emerging, which might obviate the need for fragment retrieval in some patients. 64,65 Finally, the routine deployment of a UAS is not without its risks. 66 Until level 1 evidence for the safety and effectiveness of this procedure emerges, the indications for use of a UAS and retrieval will likely remain very much influenced by both patientrelated and stonerelated factors.…”
Section: Active Retrieval Of Fragmentsmentioning
confidence: 99%
“…More recently, newer laser lithotripsy techniques such as dusting utilizing highwatt holmium systems have been popularized. 15 Dusting uses a high-frequency, low-pulse energy setting, such as 30-50 Hz · 0.2-0.5 J, which seeks to fragment stones to fine powder and small fragments, and thus reduce the need to retrieve fragments. We were surprised to find out that twothirds of respondents indicated using this technique.…”
Section: Discussionmentioning
confidence: 99%
“…We found that using 60 W from the start for all stones produced large fragments if the stone was fragile. Numerous large fragments may significantly increase the operative time, require an additional step for removal or the use of a specific laser technique, such as the 'popcorn effect', to reduce the stone burden [13]. Therefore, we recommend starting with 40-W power to produce small fragments and to increase the power to 60 W if the speed of disintegration is not satisfactory in cases of hard stones.…”
Section: Discussionmentioning
confidence: 99%